قراءة في الحركة العلمية بتلمسان الزيانية 633هـ -992هـ الموافق لـ 1236م-1554م - مغنيـة, غردايــن (Sciences de l'Homme et de la Société; Vol. 24 (2017): SCIENCE DE L'HOMME ET DE LA SOCIETE (Sep 2017), 2017)
شهدت تلمسان الزيانية نظامان في التعليم، النظام الابتدائي والنظام الاحترافي، وكان المتعلمون يتلقون دروسهم في كلا النظامين بمؤسسات مختلفة كالكتاتيب، المساجد والمدارس وهي نوع المؤسسات التعليمية التي تأخر ظهورها بتلمسان الزيانية الى مطلع القرن الثامن هجري الموافق للقرن الرابع عشر ميلادي كمدرسة ابني الامام، المدرسة التاشفينية كما اعتبرت الزوايا أيضا ضمن المؤسسات التعليمية ذات الطابع الديني والثقافي، ومن أهم العلوم التي انتشرت بتلمسان الزيانية، علم التفسير، وعلم الحديث والفقه واللغة والأدب والتاريخ والطب مما جعل تلمسان تحظى بنصيب كبير في استقبال العلماء وارسال علماء من والى مختلف أنحاء بلاد المغرب الاسلامي خاصة الأندلس .                                                                                                                                               Abstract : Tlemcen during the zianid dynasty experienced two systems of education, the primary and the professional cycle. The disciples received their course in the two cycles at the breasts of the different institutions like the medersas; mosques, and schools. This type of institution, which appeared only at the beginning of the eighth century hijjri, corresponding to the fourteenth century after I, like the college of bn el imam and medersa tachfinya, the zawiyas were considered to be religious and cultural educational institutions. The most important sciences that tlemcen zianide has known are ... .. al hadith, ... .. Attafir, jurisprudence, language, literature, history and medicine. All this has qualified Tlemcen to become a prestigious scientific pole that receives and sends sch